Linguistic Potentialities in Eliot's New Idea about the Old Concept “Classic” - Leila Aghayani Chavoshi (مطالعات زبانی و بلاغی)
T. S. Eliot, the father of new criticism, took into consideration an important subject in his literary arguments and approaches, something not much regarded and analyzed. That which can be an important criterion in valuating literary works and considered as a guidance for creating eminent literary works. In his new approach he described the works which as he called are “classic” ones. Such a work is not a classic one due to its antiquity or being compatible with the principles of classicism (school art of 18th century).  According to Eliot a “classic” work is an outstanding literary work with excellent characteristics. These characteristics give the classic works an intrinsic value, beyond the accepted artistic, social and cultural principles of the time they are created in. In his view, classics possessed a special perfection and richness or as he expressed “maturity” in three aspects: maturity of language, maturity of culture, and maturity of writer. Because of these features classics can be accepted by readers of different cultures and countries and also in different times.